PELAKSANAAN PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA EKSPLOITASI EKONOMI DI KOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Economic poverty has created a lot of child labor, where the parents order their children to help the family's economy and those who deliberately took advantage of them for personal gain due to economic factors, which resulted in the loss of children's rights. In essence, a child cannot protect themselves from various kinds of actions that cause harm, such as mental, physical, and social losses in various fields of life and livelihood. Children must be assisted by others to protect themselves, given the situation and condition. Therefore, the implementation of child protection is an obligation and responsibility of the State, Government, Regional Government, Community, Family, and Parents or Guardians.This type of research is sociological legal research, where the author directly researches the location under study to provide a complete and clear picture of the problem being studied, this research was conducted on the streets of Pekanbaru, Pekanbaru Resort Police, and Pekanbaru Social Service. The population and sample are all parties related to the problems studied in this study, the data sources used are primary data, secondary data, and tertiary data, data collection techniques in this study are observation, interviews, and literature study.There are several results of the study that can be concluded. First, the rights of children as victims have not been truly fulfilled, aside from that the implementation of legal protection for children as victims of economic exploitation crimes in Pekanbaru regulated in the Child Protection Act has not been optimal. Second, the obstacles in the implementation of legal protection are caused by the lack of cooperation between child care institutions, the insensitivity of the community, the lack of legal awareness, and economic factors. Keywords: Legal Protection, Children, Economic Exploitation Crime